Identities and Intimacies on Social Media Transnational Perspectives - Krijnen, Tonny; Nixon, Paul; Ravenscroft, Michelle; Scarcelli, Cosimo Marco (Interdisciplinary Research in Gender, 2023)
This edited collection illuminates the scope with which identities and intimacies interact on a wide range of social media platforms. A varied range of international scholars examine the contexts of very different social media spaces, with topics ranging from whitewashing and memes, parental discourses in online activities, Spotify as an intimate social media platform, neoliberalisation of feminist discourses, digital sex work, social media wars in trans debates and 'BimboTok'. The focus is on their acceleration and impact due to the specificities of social media in relation to identities, intimacies within the broad 'political' sphere. The geographic range of case study material reflects the global impact of social media, and includes data from Belgium, Canada, China, France, Germany, Greece, Italy, Portugal, Spain, Sweden and the USA. This enlightening and rigorous collection will be of key interest to scholars in media studies and gender studies, and to scholars and professionals of social media. The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license.